MAPK Pathway Inhibitors Sensitize BRAF Mutant Melanoma to an Antibody-Drug Conjugate Targeting GPNMB - Rose, April A. N. (Clin Cancer Res, 2016)
PURPOSE: To determine if BRAF and/or MEK inhibitor-induced GPNMB expression renders melanomas sensitive to CDX-011, an antibody-drug conjugate targeting GPNMB. EXPERIMENTAL DESIGN: The TCGA melanoma dataset was interrogated for a panel of MITF-regulated melanosomal differentiation antigens, including GPNMB. BRAF mutant melanoma cell lines treated with BRAF or MEK inhibitors were assessed for GPNMB expression by RT-qPCR, immunoblot and FACs analyses. Transient siRNA-mediated knockdown approaches were used to determine if MITF is requirement for treatment-induced GPNMB upregulation. GPNMB expression was analyzed in serial biopsies and serum samples from melanoma patients taken before, during and after disease progression on MAPK inhibitor treatment. Sub-cutaneous injections were performed to test the efficacy of MAPK inhibitors alone, CDX-011 alone, or their combination in suppressing melanoma growth. RESULTS: A MITF-dependent melanosomal differentiation signature is associated with poor prognosis in patients with this disease. MITF is increased following BRAF and MEK inhibitor treatment and induces the expression of melanosomal differentiation genes, including GPNMB. GPNMB is expressed at the cell surface in MAPK inhibitor-treated melanoma cells and is also elevated in on-treatment versus pre-treatment biopsies from melanoma patients receiving MAPK pathway inhibitors. Combining BRAF and/or MEK inhibitors with CDX-011, an antibody-drug-conjugate targeting GPNMB, is effective in causing melanoma regression in pre-clinical animal models and delays the recurrent melanoma growth observed with MEK or BRAF/MEK inhibitor treatment alone. CONCLUSIONS: The combination of MAPK pathway inhibitors with an antibody-drug-conjugate targeting GPNMB is an effective therapeutic option for patients with melanoma.